A Critical Discourse Analysis of Political Speech of Four Candidates of Rasht City Council Elections in 2013, with a View to Fairclough Approach - Jalali, Mahshid Sadat Naghibzadeh; Bahador Sadeghi (European Journal of Social Science Education and Research, 2014)
The current study is based on a Critical Discourse Analysis (CDA) approach of Rasht City Council Candidates' speeches, slogans, posters, and other campaign and propaganda tools used to take part in City Council Elections. Four candidates were selected in this study from whom two candidates were finally successful in the City Council Elections and the other two were not. All of four candidates had different academic education, working records, behavioral characteristics and thought tendencies. They filled a questionnaire prepared by the researcher containing their biographical information, purposes, motivations, kinds of political propaganda, organizational or other kinds of support, if any, and something else. Researcher also used a controlled interview asking some questions about the important factors influenced on the candidates' succession or fails including occupation, thought tendency, type of sloganeering, discourse techniques and so on. It should be noted that researcher considered some available sloganeering instruments like posters, CDs of lectures, pictures and slogans used by the candidates in Rasht City Council Election Process. Then the collected data were analyzed and compared to each other to identify the candidates' thoughts and ideas represented in their speeches. Based on Fairclough framework, this study investigates how the candidates try to justify their ideas and persuade their audiences by utilizing suitable ideological discourse structures in their speeches. Also the aim of this paper is to analyze and compare the candidates' speeches in order to discover the ideological strategies, power relations and persuasive techniques underlying their speeches and to identify the most important factors influenced on their success and fail.
Keywords: Discourse Analysis (DA), Critical Discourse Analysis (CDA), Political Discourse, Rasht City Council Elections